Bacterial plant pathology : - Sigee, David C. (Cambridge University Press, 1992)
Bringing together bacterial structure and function, taxonomy, environmental microbiology, induction and development of plant disease, molecular genetics and disease control, Dr Sigee unifies the field, at the same time as emphasising exciting developments in cell and molecular biology. The book is written in a clear and concise manner, illustrated with numerous tables, diagrams and photographs.